Chemical and microbiological characterisation of "Salpicao de Vinhais" and "Chourica de Vinhais": traditional dry sausages produced in the North of Portugal - Ferreira, Vânia (2010)
"Chouriça de Vinhais" and "Salpicão de Vinhais" are traditional smoked naturally fermented meat products produced in the North of Portugal, Trás-os-Montes. The objective of this study was the characterisation of these products, giving particular attention to their microbiological and chemical safety. Nitrite, nitrate, heavy metals and biogenic amines were within accepted limits for meat products. Globally, the need for improvements in the good manufacturing practices was demonstrated in this study as various lots were considered of unsatisfactory microbiological quality according to the guidelines published by the Food Safety Authority of Ireland.